ANALISIS YURIDIS TERHAHADAP PP NO. 6 TAHUN 2010 TENTANG SATUAN POLISI PAMONG PRAJA DI PROVINSI KEPULAUAN RIAU - Syrief, Elza; Sudirman, Lu; Saputra, Dedi Eka (Journal of Judicial Review, 2010)
The abstract in this article is available in printed form.